HİBRİT SAVAŞ STRATEJİLERİ - Atun, Ata; Atun, Yurdagül; Zort, Çağın (TURAN : stratejik arastirmalar merkezi, 2025)
Hybrid warfare strategies provide a framework that reflects the complex nature of modern military actions. In the period when the global security environment is evolving, asymmetric tactics and cyberattacks are also used in addition to classical combat methods. This strategy includes elements such as social engineering, disinformation and economic pressure in addition to physical conflicts. Today, hybrid warfare is an indispensable tool that provides flexibility for military and political leaders. Today, hybrid warfare practices indicate a period in which states, private military companies and terrorist groups are pushing the boundaries of conventional warfare. This situation reveals that in addition to classical military strategies, information management, media manipulation and local dynamics on the field are also important. As a result, hybrid warfare is a dynamic structure that emerges with the synergy of different types of warfare and has become one of the most important elements to be considered in today's global security environment.